Digital Tabarruj: The Phenomenon of Muslim Women Adorning Themselves on Social Media from a Contemporary Tafsir Perspective (Analysis of QS. Al-Ahzab/33:33 and QS. An-Nur/24:31) - Aina Rohmatul Ummah; Abdul Fatah; Althaf Husain Muzakky (Insitut Muslim Cendekia, 2025)
The phenomenon of digital tabarruj has become a pressing social phenomenon in the modern visual era because it reveals the tension between religious piety and online self-expression. Contemporary tafsir studies attempt to address this issue by recontextualizing the prohibition of tabarruj as a moral ethic for digital culture. This research aims to reinterpret QS. Al-Ahzab/33:33 and QS. An-Nur/24:31 through a combination of Tafsir Al-Maraghi and Fazlur Rahman's Double Movement theory, which methodologically allows for a connection between the normative meaning of the text and the current social context. The research method uses a qualitative approach based on literature studies and digital literature. The research findings indicate that the moral principles of the verse, from the context of the Jahiliyyah era to the digital age, emphasize simplicity, honor, and self-control in adornment. The novelty of this study lies in the application of double-movement hermeneutics to articulate the ethics of Muslim women's adornment in digital space, while also offering theoretical implications for the development of contextual interpretation and practical implications for the formation of digital ethics literacy based on Islamic values of modesty.